2008
DOI: 10.1007/s10802-008-9272-2
|View full text |Cite
|
Sign up to set email alerts
|

Early Childhood Adversities and Trajectories of Psychiatric Problems in Adoptees: Evidence for Long Lasting Effects

Abstract: The aim of the present study is to investigate whether early childhood adversities determine the longitudinal course of psychiatric problems from childhood to adulthood; in particular if the impact of early maltreatment on psychopathology decreases as time passes. A sample of 1,984 international adoptees was followed (955 males and 1029 females; adopted at the mean age of 29 months). Parents provided information about abuse, neglect and number of placements prior to adoption at baseline and completed the Child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
58
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(65 citation statements)
references
References 48 publications
5
58
0
1
Order By: Relevance
“…The fact that all the adoptees in the sample were actively searching for their biological families may explain why they did not show adoption-process avoidance. These results also support Pavio and Patteson (1999) results about the long term consequences of child abuse in poor social adjustment and isolation feelings, and extend the consequences of maltreatment after maltreatment episodes well beyond the 28 years reported by Van der Vegt et al (2009). In our study, maltreatment was combined with traumatic revelation of adoptee status in a part of the sample, and this combination produced a stronger effect in posttraumatic symptoms.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The fact that all the adoptees in the sample were actively searching for their biological families may explain why they did not show adoption-process avoidance. These results also support Pavio and Patteson (1999) results about the long term consequences of child abuse in poor social adjustment and isolation feelings, and extend the consequences of maltreatment after maltreatment episodes well beyond the 28 years reported by Van der Vegt et al (2009). In our study, maltreatment was combined with traumatic revelation of adoptee status in a part of the sample, and this combination produced a stronger effect in posttraumatic symptoms.…”
Section: Discussionsupporting
confidence: 91%
“…Also, studies in internationally adopted samples demonstrated the effect of early adversities on mental health problems in childhood, adolescence and adulthood (Cederblad, Höök, Irhammar & Mercke, 1999;Fensbo, 2004;Hoksbergen, 1997;Juffer & IJzendoorm, 2005). Finally, a study by Van der Vegt, van der Ende, Ferdinand, Verhulst and Tiemeier (2009) with internationally adopted children found no reduction in the impact of early maltreatment over a period of 28 years, from childhood to adulthood, even though the children had been taken out of their problematic environments and raised in enriching environments.…”
Section: Introductionmentioning
confidence: 97%
“…Increased cortisol levels among low SES children correlate with symptoms of depression [76,93,96], stress, or anxiety [102] among mothers, underscoring the need for a long-term solution to reduce psychosocial risk factors in these families. Both adults and adolescents with deviating CCRs (higher baseline levels and flatter slope) have retrospectively reported early childhood adversity [84,103]. Our findings of higher variability in cortisol levels, higher basal cortisol levels, and less well-defined CCRs are consistent with earlier studies [76,93,101,102], despite population differences in age.…”
Section: Cortisol In Children At High Psychosocial Risksupporting
confidence: 90%
“…Children (one to six years old), born to a normal population of healthy mothers who self-reported maternal stress, anxiety, and psychological stress during their infants' first years of life, show altered cortisol AUC and CCR development [102], as do older children (six to ten years old) of low SES whose basal cortisol levels are increased [93]. Both adults and adolescents with altered CCR (higher basal levels and flatter slope) have retrospectively reported early childhood adversity [84,103].…”
Section: High Psychosocial Risk -Insecure Attachment Cortisol Levelsmentioning
confidence: 99%
“…It has been shown for a long time that early life adversity significantly increases psychiatric vulnerability in adulthood [7]; such an effect has been replicated in many large sample studies [8,9]. High risk psychiatric conditions include depression [10], anxiety [11], substance abuse [12], as well as psychosis related disorders such as schizophrenia [13,14].…”
Section: Childhood Adversity and Psychiatric Vulnerability: Epidemiolmentioning
confidence: 95%